Contesting childhood : autobiography, trauma, and memory - Douglas, Kate, 1974- (Rutgers series in childhood studies., 2010)
Drawing on trauma and memory studies and theories of authorship and readership, Contesting Childhood offers commentary on the triumphs, trials, and tribulations that have shaped this genre. Kate Douglas examines the content of the narratives and the limits of their representations, as well as some of the ways in which autobiographies of youth have become politically important and influential. This study enables readers to discover how stories configure childhood within cultural memory and the public sphere.